Clinical effects and safety of different strategies for administering intravenous diuretics in acutely decompensated heart failure: a randomised clinical trial. Issue 9 (22nd June 2013) - Llorens, Pere; Miró, Òscar; Herrero, Pablo; Martín-Sánchez, Francisco Javier; Jacob, Javier; Valero, Amparo; Alonso, Héctor; Pérez-Durá, María José; Noval, Antonio; Gil-Román, José Juan; Zapater, Pedro; Llanos, Lucía; et al.
Abstract : Background: The mainstay of treatment for acutely decompensated heart failure (ADHF) is intravenous diuretic therapy either as a bolus or via continuous infusion. Objectives: We evaluated the clinical effects and safety of three strategies of intravenous furosemide administration used in emergency departments (EDs) for ADHF. Methods: We performed a multicentre, randomised, parallel-group study. Patients with ADHF were randomised within 2 h of ED arrival to receive furosemide by continuous infusion (10 mg/h, group 1) or boluses (20 mg/6 h, group 2; or 20 mg/8 h, group 3). The primary end point was total diuresis, and secondary end points were dyspnoea, orthopnoea, extension of rales and peripheral oedema, blood pressure, respiratory and heart rates, and pulse oximetry, which were measured at arrival and 3, 6, 12 and 24 h after treatment onset. We also measured serum creatinine, sodium and potassium levels at arrival and after 24 h. Results: Group 1 patients (n=36) showed greater 24 h diuresis (3705 mL) than those in groups 2 (n=37) and 3 (n=36) (3093 and 2670 mL, respectively; p<0.01), and this greater diuretic effect was observed earlier. However, no differences were observed among groups in the nine secondary clinical end points evaluated. Creatinine deterioration developed in 15.6% of patients, hyponatraemia in 9.2%, and hypokalaemia in 19.3%, with the only difference among groups observed in hypokalaemia (group 1, 36.3%; group 2, 13.5%; group 3, 8.3%; p<0.01). Conclusions: In patients with ADHF attending the ED, boluses of furosemide have a smaller diuretic effect but provide similar clinical relief, similar preservation of renal function, and a lower incidence of hypokalaemia than continuous infusion. Trial registration number: This randomised trial was registered in the European Clinical Trial Database (EudraCT) with the reference number 2008-004488-20.